Complete mitochondrial genome of Polybranchia orientalis sp. nov. from the South China Sea - Mao, Mingguang; Wang, Yaru; Jiang, Jielan; Tang, Xiangcheng; Geng, Xiaoming (Frontiers in Marine Science, 2025)
A species of sea slug discovered in the South China Sea was characterized based on its morphology, mitochondrial genome, and phylogenetic position. The slug exhibits brown coloration, resembling seaweed. It features detachable, feather-like cerata capable of independent movement. The mitochondrial genome (14,452 bp; GenBank accession: PV637185) contains 13 protein-coding genes (PCGs), 22 tRNAs, 2 rRNAs, and a non-coding control region. Nucleotide composition showed a strong AT bias (65.55%), with AT-skew and GC-skew values of -0.1421 and 0.0607, respectively. Phylogenetic based on the cytochrome c oxidase subunit I (cox1) gene sequence analysis revealed a close relationship with Polybranchia orientalis, while BLAST analysis demonstrated high similarity between the cox1 gene of this sea slug and that of P. orientalis. Since the complete genome sequence of P. orientalis is currently unavailable, an additional phylogenetic analysis was performed using the 13 protein-coding genes (PCGs) of other sea slugs, which showed that this species clustered within a clade comprising several other species of the family Plakobranchidae. Integrating cox1 sequence data and morphological evidence, we assign this slug to the species Polybranchia orientalis sp. nov. Interestingly, the cerata exhibit green pigmentation, and algal chloroplast genes were detected within them, suggesting kleptoplasty.